PENGARUH PENERAPAN SISTEM MONITORING PELAPORAN PEMBAYARAN PAJAK (MP3) TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK (STUDI EMPIRIS PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAWA BAGIAN TIMUR I) - Lasmana, Mienati Somya; Narsa, I Made; Sawarjuwono, Tjiptohadi (UI Scholars Hub, 2005)
This study is an empirical research conducted on the taxpayers at the Directorate General of Taxation Office - East Java Region I. The objectives ae: (1) to obtain empirical evidence on whether the implementation of MP3 system was perceived in accordance with the taxpayer expectation in fulfilling their tax obligations. (2) To empirically examine whether the Monitoring Statement/Report of Tax Payment (MP3) in simplifying tax payment service for the taxpayers affects the taxpayer satisfaction. (3) To empirically examine whether the implementation of MP3 system increase the taxpayer satisfaction. (4) To seek and examine empirically whether the taxpayer satisfaction rate positively and significantly affected the taxpayer compliant rate. The design of the research was a survey method. There are 138 samples drawn at randomly from 12.300 taxpayers at the Directorate General of Taxation Office - East Java Region I. Quantitative approach was employed in analyzing the data to test the four hypotheses proposed. Binomial and regression tests were conducted to test these hypotheses. The variables of the research consisted of: implementation of MP3 system (X1), Taxpayer Satisfaction Rate (Yi), and Taxpayer Compliant Rate (Y2). The result of the research shows that the MP3 system is not suitable yet with the taxpayer expectations. While the second, third and fourth hypothesis are proven. The MP3 system strongly and significantly correlates with the satisfaction Pengaruh Penerapan Sistem Monitoring Pelaporan Pembayaran Pajak (MP3) terhadap 131 Tingkat Kepatuhan Wajib Pajak (Studi Empiris pada Kantor Wilayah Direktorat Jenderal Pajak Jawa Bagian Timur I) and compliant rates. It is also proven that the implementation of MP3 system positively and significantly correlates with the taxpayer compliant rate.